Use of Z-plasty in the treatment of severe colostomy stenosis - Mladenovikj, Dragoslav; Ristovski, Slobodan (Lietuvos chirurgija, 2017)
Stenosis of stoma is late complication after colostomy in about 1–13% of the patients. The severe colostomy stenosis needs surgical treatment because resulting bowel obstruction with possibility of emergency operation and serious complications. In four year period we treated 7 patients with severe colostomy stenosis with Z-plasty according Lyons and Symon technique. All the treated stenoses were end-colostomies resulted from abdominal-perineal resection of the rectum for adenocarcinoma. There were no intra and postoperative complications, with good functional results and without recurrences of the stenosis within follow-up period of the 6-36 months. Z-plasty is easy and safe procedure for stenosis of the stoma after end-colostomy. This extra-abdominal procedure used on day-surgery basis, eliminate possibility for intraperitoneal complications.